The dialectal image of family ballads from the Porabje region - Koletnik, Mihaela (Jezikoslovni zapiski, 2023)
The paper presents the findings of a dialectal analysis of the Porabje family ballads published in the fifth book of Slovenske ljudske pesmi (Slovenian folk songs) (2007). In Porabje, eight types of family ballads, with 59 variants, were recorded. In some we find typical Prekmurje phonological, morphological and lexical features as already known from the fieldwork and the findings based on the study of the Porabje local dialects. Other still are either moving in the direction of a (regional) supradialect or are fairly close to the literary language.